2007
DOI: 10.1021/jp072927s
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitization of TiO2 and SnO2 by Artificial Self-Assembling Mimics of the Natural Chlorosomal Bacteriochlorophylls

Abstract: Of all known photosynthetic organisms, the green sulfur bacteria are able to survive under the lowest illumination conditions due to highly efficient photon management and exciton transport enabled by their special organelles, the chlorosomes, which consist mainly of self-assembled bacteriochlorophyll c, d, or e molecules. A challenging task is to mimic the principle of self-assembling chromophores in artificial light-harvesting devices. In the present work we have studied exciton transport and dissociation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 67 publications
0
57
0
Order By: Relevance
“…Artificial self-assembling chromophores, which mimic the chlorosomal BChls, do not have this disadvantage and are good candidates for incorporation into hybrid solar cells (23,24).…”
Section: Thementioning
confidence: 99%
See 1 more Smart Citation
“…Artificial self-assembling chromophores, which mimic the chlorosomal BChls, do not have this disadvantage and are good candidates for incorporation into hybrid solar cells (23,24).…”
Section: Thementioning
confidence: 99%
“…The self-assembly algorithm programmed within chlorosomes could be reproduced with completely artificial pigments (18)(19)(20)(21)(22), that lends hope that it can be used in solid-state devices such as hybrid solar cells (23,24). This would enable efficient light capturing and operation also under lowlight illumination conditions.…”
mentioning
confidence: 99%
“…The only works that we could found were performed of TiO 2 -containing hybrid systems such as TiO 2 -SiO 2 -POM [72] and g-C 3 N 4 -Mn þ /CeO 2 -TiO 2 [73]. This was accompanied by works involving photosensitization of oxides such as WO 3 and (surprisingly) SiO 2 [74] as well as SnO 2 [75]. The only exception we found (an exception that hopefully is the first sign of a change) was a manuscript on the origin of slow carrier transport in thin films photoanodes made of BiVO 4 [76].…”
Section: Transient Measurementsmentioning
confidence: 99%
“…Many challenges exist in enhancing photoinduced activity of TiO 2 , or increasing spectral sensitivity of TiO 2 to visible light. Ion doping [60] , ion implantation [61] , composite semiconductor [62] , noble metal deposition [63] , photosensitization [64] and other modification methods have been used for reducing the combination of electron-hole pairs or extending the threshold of exciting wavelength. Recently, several researchers found that the morphology of TiO 2 had a strong relationship with its photoactivity, and some work had been done for the synthesis of TiO 2 with 1D structure [65] , nanospheres structure [66] , nanoflowers structure [67] etc.…”
Section: Future Perspectivesmentioning
confidence: 99%